Menggapai Asa Melalui Pendidikan: Studi Lima Mahasiswa Dan Keluarganya Di Desa Palece Kabupaten Polewali Mandar - Nurchumairah Putri; Mauliadi Ramli (Rayhan Intermedia, 2023)
This study aims to reveal the efforts of students and their families in the struggle to obtain education for the betterment of their destiny. researchers used a type of descriptive qualitative research. The selected informants were students and their parents who came from low-income backgrounds. The researchers collected data by means of observation, interviews and documentation. The results of the study show that there are: 1) Student strategies in continuing education, namely students registering for tertiary institutions with the choice of SNMPTN, SBMPTN and independent pathways, following suggestions from teachers regarding tips for college entrance exams, using social media to gain knowledge related to college exam material , carry out teaching practice as an entry requirement from the chosen major, and administer the bidikmisi program as payment assistance each semester. 2) Students try to carry out learning activities individually and in groups, keep working on class assignments and take part in activities outside the campus, having side jobs such as sewing and selling online. Even though he works, he still prioritizes education by completing college assignments first and then continuing his work. 3) The family's economy has decreased because they initially lacked the economy and for daily life they have to do their best to provide for the basic needs of the family and there are even among student families who have to seek loans from other people to be able to finance their family needs.